Authorities and environmental organizations in the light of the administrative law - Jabłoński, Maciej (Studia Ecologiae et Bioethicae, 2012)
The case-law of the administrative courts of law practice reflected in the field of environmental law and its regulation by the public administration. Issues that have been taken and implemented by the legislative bodies were subsequently clarified by case law and specific administration. It is appropriate to be able to correlate the legislative and administrative law in order to give common guidelines for the application of the law by the actors and institutions in the field of environmental protection.